Assessment of the Impact of the Covid-19 Pandemic on the Incomes and Adaptation of the Population of the Region To It: Statistical Approach - N. D. Kremlev; I. A. Drozdova (Статистика и экономика)
The aim of the study is to determine the impact of the COVID-19 pandemic and the self-isolation regime announced in Russia on the incomes of the population. The relevance of the study is connected with the problems of reflecting the pandemic, searching for patterns and its interrelations with incomes, health, living conditions of the population. The emergence of coronavirus disease (March 2020), quickly spread to all regions of the country, in 2021 the fourth record wave of morbidity and mortality of the population was recorded.The research methods are the theory and methodology of income of the population used by the Federal State Statistics Service, corresponding to international norms and standards, including the system of national accounts. To determine the directions of the impact of the COVID-19 pandemic on the incomes of the population of the region, the method of analytical groupings (stochastically deterministic relationships), as well as the method of comparing parallel series, the index method and interregional data evaluation analysis were used.The results of the study: the use of a statistical approach to assess and determine the impact of the COVID-19 pandemic on the real incomes of the population allowed us to determine the features of the spread of the disease in the regions of the Ural Federal District. The conclusion is made: the spread of COVID-19 in 2020-2021 did not have a significant impact on the real monetary incomes of the population in the regions of the Ural Federal District, despite the increase in the morbidity of people. The population quickly adapted to the pandemic, many enterprises were operating normally, and the state took prompt measures to reduce tensions and support the population and the health system in the country. The oppositely directed factors of the impact of the pandemic, leading to negative and positive consequences of real incomes of the population, have been identified. The level and degree of influence of the morbidity of the population on the income of the population are determined.Conclusion: the use of a statistical approach makes it possible to improve the quality of information, to determine the positive and negative factors of the COVID-19 pandemic’s impact on incomes and the level of adaptation of the region’s population to it. The adaptation of the population to the coronavirus will continue for several more years and longer, and the waves of the disease will decrease as medicines are created. The study makes it possible to assess not only the main directions of influence on the real monetary incomes of the population, but also the quality of decisions made by management structures.